Noninvasive Free Flap Monitoring Using Eulerian Video Magnification - Yuan Fang Liu; Christopher Vuong; Paul Charles Walker; Nathaniel Ray Peterson; Jared Christian Inman; Pedro Alcantara Andrade Filho; Steve Choon-Sung Lee (Case Reports in Otolaryngology)
Eulerian Video Magnification (EVM) can enhance subtle changes in videos to reveal what was once invisible to the naked eye. In this proof of concept study, we investigated using EVM as a novel form of free flap monitoring. Free flaps with skin paddles were filmed in the operating room with manipulation of their pedicles. In a representative 77-year-old female who received a latissimus dorsi-serratus-rib composite free flap, EVM was able to detect blockage of arterial or venous supply instantaneously, providing a visible representation through degree of color change in videos. EVM has the potential to serve as a powerful free flap monitoring tool with the benefit of being noninvasive, sensitive, easy-to-use, and nearly cost-free.